2011
DOI: 10.1523/jneurosci.6513-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Phosphatase Activity Attenuates α-Synucleinopathy in a Mouse Model

Abstract: α-Synuclein (α-Syn) is a key protein that accumulates as hyperphosphorylated aggregates in pathologic hallmark features of Parkinson’s disease (PD) and other neurodegenerative disorders. Phosphorylation of this protein at serine 129 is believed to promote its aggregation and neurotoxicity suggesting that this post-translational modification could be a therapeutic target. Here, we demonstrate that protein phosphatase 2A (PP2A) dephosphorylates α-Syn at serine 129, and that this activity is greatly enhanced by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
193
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 163 publications
(214 citation statements)
references
References 63 publications
(74 reference statements)
15
193
2
4
Order By: Relevance
“…The ability of EHT, which prevents the demethylation of PP2A, in reducing α ‐synuclein phosphorylation and aggregation associated with improved neuropathological abnormalities and behavioral deficits in α ‐synuclein transgenic mice 13 supports this conclusion. Enhancing PP2A activity has also been shown to mitigate the pathology in an AD model as well: EHT treatment resulted in substantial amelioration of AD‐like pathologies such as tau hyperphosphorylation, elevated amyloid‐ β levels, and cognitive impairment in a rat model of AD generated by viral vector‐mediated expression of the PP2A endogenous inhibitor I2 PP2A , or SET protein, in the brain 19.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The ability of EHT, which prevents the demethylation of PP2A, in reducing α ‐synuclein phosphorylation and aggregation associated with improved neuropathological abnormalities and behavioral deficits in α ‐synuclein transgenic mice 13 supports this conclusion. Enhancing PP2A activity has also been shown to mitigate the pathology in an AD model as well: EHT treatment resulted in substantial amelioration of AD‐like pathologies such as tau hyperphosphorylation, elevated amyloid‐ β levels, and cognitive impairment in a rat model of AD generated by viral vector‐mediated expression of the PP2A endogenous inhibitor I2 PP2A , or SET protein, in the brain 19.…”
Section: Discussionmentioning
confidence: 53%
“…Considering the deleterious consequences of a dysfunctional PP2A, it is unlikely that the changes observed in these postmortem brain analyses represent a protective effect in surviving neurons. In relation to α ‐synucleinopathies in particular, PP2A catalyzes the dephosphorylation of phospho‐Ser 129 α ‐synuclein, and the methylation state of the PP2A C subunit regulates this activity 13. Accordingly, the finding of decreased PP2A methylation in this study provides a molecular mechanism for the reduced PP2A activity reported in α ‐synucleinopathies 16 and is likely a significant contributor to the hyperphosphorylation of aggregated α ‐synuclein in these disorders 10, 29…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations